HERMENEUTIKA KHALED ABOU EL FADL; SEBUAH KONTRIBUSI PEMIKIRAN DALAM STUDI ISLAM - Wardi, Moh. (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2014)
This writing discusses Khaled Abou El Fadl’s thought about hermeneutic phenomena responses to the spreading of otoritarianism in law discourses from islamic contemporary. He tried to interpret the doctrines about female moslem life in Saudi Arabia, Generally, a bias doctrines about gender stated by Islamic law experts to CRLO (Permanent Council for Scientific Research and Legal Opinions).in approaching the hermeneutic, at least, it involved three variables they are author (pengarang),text (teks), dan reader (pembaca). Interpretation method developed by Abou El Fadl is dynamic interpretation (lively interpretative) That interpreters not only understood a previous definition as al-qur’an verses given in the context of socio-histories. But, It’s more than that, the interpreters had also dug text definition in latest context.